Military autonomy: its origins, limits, and the politico-military dialectic of war. Issue 3 (3rd July 2019) - Campbell, Peter
ABSTRACT: Military officers often oppose political interference in the conduct of war. Political leaders respond by citing Clausewitz's contention that "war is the continuation of politics with the addition of other means." Scholarship in security studies and civil-military relations argues that civilians are right to oppose military autonomy because it serves the parochial interests of the military. However, through the dialectical relationship between the violent essence of war and its political nature, Clausewitz provides an alternative explanation for military demands for autonomy. He shows that military and political leaders are prone to an incomplete understanding of war that can undermine strategy and policy.